Similar active genes cluster in specialized transcription factories - Xu, M; Cook, P (Rockefeller University Press, 2008)
How transcription affects the way specific genes are arranged within the nucleus remains to be fully understood. We examine here whether transcription occurs in discrete sites (factories) containing the required machinery and whether these sites specialize in transcribing different genes. We cotransfected plasmids encoding a common origin of replication but different transcription units into cells, where they are assembled into minichromosomes that the cellular machinery replicates and transcribes. In cells containing thousands of minichromosomes, we found (using fluorescence in situ hybridization) active templates concentrated in only a few factories that transcribe particular units depending on the promoter type and the presence of an intron. Close proximity between similar transcription units, whether on two different microchromosomes or on host chromosomes and minichromosomes, is confirmed using chromosome conformation capture. We conclude that factories specialize in producing a particular type of transcript depending on promoter type and whether or not the gene contains an intron.